State interventions and natural resource management: A study on social interfaces in a riverine fisheries setting in Kerala, India - Sunil D. Santha (Natural Resources Forum 31 (2007) 61-70, 2007)
This article attempts to analyse the social interface between formal institutions and local fishing communities along the Pamba-Achankovil River Basin in Kerala, India. It Examines primarily the nature of the relationship between state agencies and traditional Fishing communities in the context of (i) enforcing certain formal regulations of resource use and (ii) implementing resource enhancement programmes. The article also analyses the nature of social interfaces that emerge when local level formal organizations, such as cooperatives and gram panchayats, take up resource management or communitywelfare schemes on behalf of the traditional fisherfolk in the study region. Social interfaces can be understood in terms of social processes, such as cooperation, accommodation and conflicts between various actors involved in fisheries management. The article is based on ethnographic fieldwork. Interview guides and focus group discussions were the primary tools of data collection. The findings show that the relationships between formal institutions and traditional riverine fishing communities lack mutual trust. Conflicts between fishing communities and state agencies emerge when the formal institutions threaten or contradict those elements of local culture that sustain livelihood needs. Conflicts and discontent with a particular formal institution can also lead to the modification or violation of coexisting institutional arrangements